Where is the Authenticity? Analyzing and Creating Representation and Inclusion of Marginalized Voices in Television and Film - Romero, Gabriela R. (Tufts Archival Research Center, 2020)
There is a disconnect between who we see on screen and the viewer. The purpose of this thesis is to investigate how representation on screen has changed over time and in what ways it can be improved.